2022
DOI: 10.7759/cureus.32659
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of Endovascular Treatment in Patients With Acute Ischemic Stroke With Large Vessel Occlusion: Mothership Versus Drip-and-Ship Model in a Portuguese Urban Region

Abstract: IntroductionEndovascular treatment (EVT) with mechanical thrombectomy and acute carotid stenting has become an integral part of the treatment of acute ischemic stroke with large vessel occlusion. Despite being included in the most recent stroke guidelines, only comprehensive centers can offer EVT and thus patients frequently need to be transferred from primary hospitals. We aimed to assess which pre-hospital model of care -direct admission to a comprehensive stroke center (mothership) or transfer to a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous studies have shown longer times to IVT treatment associated with the use of a telestroke service versus an on-site specialist, despite favoring an increase in reperfusion treatment in cases where the patient's presence is not possible [9]. Two large-scale observational studies conducted in the USA and in Portugal that involved over 1000 patients who experienced an acute stroke also demonstrated better clinical outcomes for the DT model [10,11], as well as another conducted in Germany with a similar sample of patients to our study [12]. Hypothetical bypass modeling for the transferred patients indicated that IVT would be delayed by 12 min, but the MT would be performed 91 min earlier if the patients were directly routed to the TC [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown longer times to IVT treatment associated with the use of a telestroke service versus an on-site specialist, despite favoring an increase in reperfusion treatment in cases where the patient's presence is not possible [9]. Two large-scale observational studies conducted in the USA and in Portugal that involved over 1000 patients who experienced an acute stroke also demonstrated better clinical outcomes for the DT model [10,11], as well as another conducted in Germany with a similar sample of patients to our study [12]. Hypothetical bypass modeling for the transferred patients indicated that IVT would be delayed by 12 min, but the MT would be performed 91 min earlier if the patients were directly routed to the TC [11].…”
Section: Discussionmentioning
confidence: 99%